Komunikasi Asertif Penyandang Disabilitas Fisik di Pusat Pelayanan Sosial Griya Harapan Difabel Dinas Sosial Provinsi Jawa Barat - Pribowo; Fadilah, Naila; Wibawa, Catur Hery (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2025)
Persons with disabilities represent a significant minority group that often faces barriers in interaction and full participation in society. This study aims to describe assertive communication among persons with physical disabilities at the Griya Harapan Difabel Social Service Center. The focus includes seven aspects: expressing opinions, giving and receiving positive and negative feedback, assertively refusing requests, making non-controlling requests, managing confrontation constructively, and nonverbal behavior. A qualitative descriptive approach was used, involving five informants: three service users, one social worker, and one dormitory supervisor. Data were collected through in-depth interviews, observation, and documentation. The results show that persons with physical disabilities tend to express opinions only in safe and familiar situations, openly receive praise through positive expressions, and accept criticism well when delivered politely. Refusals are conveyed directly and briefly, usually when strong reasons exist. Requests for assistance are commonly related to physical limitations. In conflict situations, they tend to avoid confrontation and suppress emotions. Nonverbal behavior reflects a closed communication style, particularly in formal settings or with unfamiliar individuals. Overall, assertive communication skills among persons with physical disabilities have not yet developed optimally and consistently. Factors such as low self-confidence, social atmosphere, and the closeness of relationships influence their communication patterns. Therefore, ongoing support and training are necessary to foster courage, assertiveness, and stability in both verbal and nonverbal communication.